Sensitive and Adaptable Turn-On Maturation (ATOM) Fluorescent Biosensors for Detecting Subcellular Localization of Protein Targets in Cells - Harsimranjit Sekhon; Jeung- Ha; Stewart Loh (Bio-Protocol)
Fluorescent protein biosensors (FPBs) that turn on—go from dark to bright upon binding their ligands—enable the detection of targets in living cells with high sensitivity and spatial localization. Several approaches exist for creating turn-on FPBs, most notably the method that gave rise to the GCaMP family of genetically encoded calcium indicators. However, it remains challenging to modify these sensors to recognize new ligands. We recently developed adaptable turn-on maturation (ATOM) biosensors, in which target recognition by a small binding domain triggers chromophore maturation in the fluorescent protein to which it is attached. ATOM sensors are advantageous because they are generalizable (by virtue of the monobody and nanobody binding domains) and modular (binding domains and fluorescent proteins of various colors can be mixed and matched for multiplexed imaging), capable of detecting endogenously expressed proteins, and able to function in subcellular compartments including the cytoplasm, nucleus, endoplasmic reticulum, and mitochondria. The protocols herein detail how to design, clone, and screen new ATOM sensors for detecting targets of choice. The starting materials are the genes encoding for a monobody or nanobody and for a cyan, yellow, or red fluorescent protein. We also present general guidelines for creating ATOM sensors using binding domains other than nanobodies and monobodies.